Adjunctive intravitreal dexamethasone in the treatment of acute endophthalmitis following cataract surgery - Edward F Hall (Dove Medical Press, 2008)
Edward F Hall1, Garrett R Scott1, David C Musch1,2, David N Zacks11Department of Ophthalmology and Visual Sciences, Medical School; 2Department of Epidemiology, School of Public Health; University of Michigan, Ann Arbor, MI, USAPurpose: Controversy exists regarding the use of intravitreal dexamethasone (IVD) as an anti-inflammatory adjunct to intravitreal antibiotics in patients with acute endophthalmitis following cataract surgery. The purpose of this project was to evaluate our experience regarding the effect of adjunctive IVD use on visual outcomes in such patients.Design: Retrospective, comparative case series.Methods: Study population: Patients treated for acute endophthalmitis following cataract surgery from 1995–2004. Intervention: In addition to standard intravitreal antibiotic treatment, some patients also received a single adjunctive injection of IVD. Primary outcome measures: Median visual acuity at last follow-up and percentage of patients achieving a ≥3-line improvement in visual acuity. Secondary outcome measures: Inflammatory index scoring, including amount of cell and flare, height of hypopyon, and presence of fibrin as a function of time after treatment.Results: Twenty-six eyes were treated with and 38 eyes without adjunctive IVD. Median presenting visual acuity was Hand Motion in both groups. Median visual acuity at last followup measured 20/40 in the IVD group and 20/50 in the No-IVD group (p = 0.75). Seventy-three percent of patients in the IVD group and 82% of patients in the No-IVD group achieved a ≥3-line improvement in visual acuity (p = 0.42). No significant difference was detected between the IVD and No-IVD groups for any of the three measures of inflammation.Conclusion: The use of IVD did not significantly improve the final median visual acuity, the chance of achieving a ≥3-line improvement in visual acuity, or the amount of intraocular inflammation. Based on these findings, and the possible detrimental effect of IVD on visual outcomes previously reported in the literature, the use of IVD does not appear to be warranted as a routine adjunctive treatment in postoperative endophthalmitis.Keywords: endophthalmitis, dexamethasone, intravitreal injection